GLP-1 Agonists Exenatide and Liraglutide: A Review About Their Safety and Efficacy - Derosa, Giuseppe; Maffioli, Pamela (Current Clinical Pharmacology, 2012)
Recently incretin-based therapies have been developed in the clinical practice, this class includes both the dipeptidyl peptidase-4 (DPP-4) inhibitors (sitagliptin, vildagliptin, saxagliptin, linagliptin), and the glucagon-like peptide- 1 (GLP-1) receptor agonists [exenatide, exenatide long acting release (LAR) and liraglutide]. In particular exenatide and liraglutide have structural similarity and bind to the GLP-1 receptor, displaying a similar broad range of activities relevant to improving glycemic control, including stimulation of insulin secretion and reduction of glucagon secretion, both in a glucose-dependent manner. Furthermore, GLP-1 slows gastrointestinal motility and increases satiety, reducing the food intake; it also promotes β-cell proliferation and probably neogenesis, while reducing apoptosis in animal models. We conducted a review analyzing clinical efficacy and safety of GLP-1 receptor agonists exenatide and liraglutide, both alone and in combination with other anti-diabetic drugs, including the most important studies about them in the latest ten years. We concluded that GLP-1 receptor agonists appear to be a good choice to decrease HbA1c levels and to lower postprandial blood glucose levels. They also suppress glucagon secretion and slow gastric motility. They also have positive effects on β-cell function and they gave a significant decrease of body weight. They are not associated with hypoglycemia, but cause a relatively high frequency of gastrointestinal disturbances, with some patients experiencing one or more episodes of nausea, vomiting, or diarrhea. However, after an evaluation of the advantages and the disadvantages, we concluded that, once metformin fails to reach an adequate glycemic control, GLP-1 receptor agonists can be a valid alternative, especially in obese type 2 diabetic patients. GLP-1 receptor agonists should be considered also in patients in therapy with metformin and another agent, such as a sulfonylurea, because of the minor risk of developing hypoglycemia and the positive effect on body weight.
Keywords: thiazolinedione